4 Eps 4 Cadmium Talk Managing cadmium levels in cocoa at the pre-harvest phase - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2025)
Moderator: Althea McKenzie. Speakers: Gideon Ramtahal and Frank Intriago